2018
DOI: 10.1186/s13068-017-1003-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Pichia pastoris for production of isobutanol and isobutyl acetate

Abstract: BackgroundInterests in renewable fuels have exploded in recent years as the serious effects of global climate change become apparent. Microbial production of high-energy fuels by economically efficient bioprocesses has emerged as an attractive alternative to the traditional production of transportation fuels. Here, we engineered Pichia pastoris, an industrial workhorse in heterologous enzyme production, to produce the biofuel isobutanol from two renewable carbon sources, glucose and glycerol. Our strategy expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
189
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(208 citation statements)
references
References 36 publications
13
189
3
Order By: Relevance
“…The isobutanol biosynthesis pathway has been engineered into various microorganisms, such as Escherichia coli [33], Saccharomyces cerevisiae [7,34], Pichia pastoris [35], Bacillus subtilis [36], Corynebacterium glutamicum [8,37], Geobacillus thermoglucosidasius [38], and Synechocystis PCC 6803 [39][40][41]. For example, Atsumi et al engineered E. coli to produce isobutanol up to 22 g/L in shake flasks [33,42], which was further increased to 50 g/L in bioreactors during batch cultures with in situ product removal by gas stripping [43].…”
mentioning
confidence: 99%
“…The isobutanol biosynthesis pathway has been engineered into various microorganisms, such as Escherichia coli [33], Saccharomyces cerevisiae [7,34], Pichia pastoris [35], Bacillus subtilis [36], Corynebacterium glutamicum [8,37], Geobacillus thermoglucosidasius [38], and Synechocystis PCC 6803 [39][40][41]. For example, Atsumi et al engineered E. coli to produce isobutanol up to 22 g/L in shake flasks [33,42], which was further increased to 50 g/L in bioreactors during batch cultures with in situ product removal by gas stripping [43].…”
mentioning
confidence: 99%
“…The vitamin solution contained 0.5 mg/L D-biotin, 1 mg/L calcium pantothenate and 1 mg/L thiamine hydrochloride. Synthetic molasses (SMs) were adapted from elsewhere [ 28 ] with modifications [ 29 , 30 ]. The SM medium contained 20 g/L sucrose (diluted molasses) for the batch fermentation phase and 100 g/L for the fed-batch process.…”
Section: Methodsmentioning
confidence: 99%
“…Microalgae are also characterized by a thicker cell wall structure made up of complex carbohydrates and glycoproteins. Jiang et al (2018) observed the cellular ultrastructure of Chlorella sorokiniana SDEC-18 under a transmission electron microscope and revealed that the plasma membrane is surrounded by a thick cell wall [ 27 ].…”
Section: Microbial Cell Wall and Lipid Compositionmentioning
confidence: 99%